Determinasi Kepemimpinan Transformasional Kepala Sekolah, Komunikasi Interpersonal, dan Motivasi Kerja Terhadap Komitmen Organisasi Guru SMA Negeri 3 Kuta Selatan - Ni Kadek Indah Permata; Kadek Rihendra Dantes; Basilius Redan Werang (LP. Ma'arif Janggan Magetan, 2024)
This study aims to 1) describe the determination of transformational leadership towards the organizational commitment of SMA Negeri 3 Kuta Selatan teachers, 2) describe the determination of interpersonal communication towards the commitment of SMA Negeri 3 South Kuta teacher organization, 3) describe the determination of work motivation towards the commitment of SMA Negeri 3 South Kuta teacher organization, 5) describe the amount of simultaneous determination of transformational leadership, interpersonal communication, and work motivation towards the commitment of the teacher organization of SMA Negeri 3 South Kuta. This study was an